ANALISIS STRATEGI MARKETING MIX DAN VOLUME PENJUALAN PADA USAHA SAOS SAMBAL GANDA SARI MUARA BULIAN - Jasasila Jasasila (Universitas Batanghari Jambi, 2017)
This study aims to determine the development of sales volume on the business of Sambal Ganda Sari Muara Bulian, to know the application of marketing mix strategy on Saos Sambal Ganda Sari Muara Bulian and to analyze Marketing Mix Strategy and Sales Volume on Saos Sambal Ganda Sari Muara Bulian. In this study the authors use descriptive and inductive data collection methods. To complete the accuracy of the results of research then in this study the authors use literature study, where the authors look for sources of information through writing both in the form of journals and articals associated with the research topic undertaken. From the analysis result, it can be seen that in general the product of sambal sauce has a good sales growth, where in the year of 2013 there is an increase of sales volume 13.65%, so also in the year 2014 there was an increase of 15.95%, significant sales volume growth occurred in 2015 where the increase reached 20.42% compared to the previous year, although in 2016 the development of Saal Sambal Ganda Sari Muara Bulian sales was not as much as the previous year which was 13.65% but the sales volume increased by 41,000 units. Strategy Marketing Mix on the road Strategy by saos sambal Ganda Sari business consists of, product strategy, Pricing Strategy, Promotion Strategy and Promotional Channel StrategyKeywords: Strategy; Marketing Mix; sales